Essential clinical anatomy - Moore, Keith L. (Lippincott Williams & Wilkins, 2011)
Essential Clinical Anatomy, Fourth Edition presents the core anatomical concepts found in Clinically Oriented Anatomy, Sixth Edition in a concise, easy-to-read, and student-friendly format. This streamlined book that includes clinical Blue Boxes, surface anatomy, and medical imaging is an excellent review for the larger text and an ideal primary text for shorter medical courses and/or health professions courses with brief coverage of anatomy.